A Little Engine that Could : Domestic Private Companies and Vietnam’s Pressing Need for Wage Employment - Steer, Liesbet (World Bank, Washington, DC, 2014)
Vietnam's young private sector is growing fast. Crucial to this growth has been a policy environment that increasingly recognizes the importance of private entrepreneurship-particularly its potential to help address the country¹s pressing need for significantly increased wage employment creation. Expanding the benefits of private sector growth beyond urban centers out into the rural areas where most Vietnamese live-and where poverty and underemployment are heaviest-will require significantly increased information flows on what is working and what is not. This paper presents an objective picture of Vietnam's emerging private sector, two years after initial implementation of the country's much praised Enterprise Law. The country's private companies are significantly better off than they were just a couple years earlier, when regional economic recession and stagnation on domestic policy reforms had brought development of the formal private sector to a near standstill. At the same time, the sector's small base means that its impressive rates of job creation still fall far short of matching the booming growth of the overall work force. Information for this paper is based on data collected from Vietnam's General Office of Statistics, a small number of individual company case studies, and a national firm-level survey designed and implemented by the authors. Research for the paper revealed significant gaps in available private sector data and flaws in current data gathering methodologies-calling into question the ability of policy makers and advisors to understand rapid, ongoing economic developments and make appropriate and timely policy decisions. The authors hope that this paper can serve as a starting point and an impetus for more targeted research aimed at identifying and addressing specific obstacles to sustainable and broad based job and wealth creation.